Mimosa (Mimosa caesalpiniifolia) prevents oxidative DNA damage induced by cadmium exposure in Wistar rats - Dias Silva, Marcelo Jose [UNESP]; Vilegas, Wagner [UNESP]; Silva, Marcelo Aparecido da; Gomes de Moura, Carolina Foot; Pidone Ribeiro, Flavia Andressa; Pereira da Silva, Victor Hugo; Ribeiro, Daniel Araki (Informa Healthcare, 2014)
The Mimosa (Mimosa caesalpiniifolia) is a plant native from South America; it is used in the traditional medicine systems for treating bacterial, fungal, parasitic and inflammatory conditions. The aim of this study was to evaluate the antigenotoxic and antioxidant activities induced by mimosa (M. caesalpiniifolia) in multiple rodent organs subjected to intoxication with cadmium chloride. A total of 40 Wistar rats (8 weeks old, 250 g) were distributed into eight groups (n = 5), as follows: Control group (non-treated group, CTRL); Cadmium exposed group (Cd); cadmium exposure and treated with extract at 62.5 mg/kg/day; cadmium exposure and treated with extract at 125 mg/kg/day; cadmium exposure and treated with extract at 250 mg/kg/day; cadmium exposure and treated with ethyl acetate fraction at 62.5 mg/kg/day. For evaluating the toxicogenetic potential of mimosa, two groups were included in the study being treated with extract at 250 mg/kg/day and acetate fraction of mimosa at 62 mg/kg/day, only. Extract of mimosa at concentrations of 62.5 and 125mg decreased DNA damage in animals intoxicated with cadmium when compared to cadmium group. In a similar manner, treatment with ethyl acetate fraction of mimosa at 62.5mg concentration in animals previously exposed to cadmium reduced genetic damage in peripheral blood cells. In a similar manner, the treatment with ethyl acetate fraction reduced DNA damage in liver cells. Oxidative DNA damage was reduced to animals exposed to cadmium and treated with 125mg of extract as well as those intoxicated to cadmium and treated with 62.5 of acetate fraction of mimosa. Taken together, our results indicate that mimosa prevents genotoxicity induced by cadmium exposure in liver and peripheral blood cells of rats as a result of antioxidant activity.
Keywords: Antioxidant activity; cadmium; genotoxicity; mimosa; rat